A Comparison of Fish Oil Sources for Parenteral Lipid Emulsions in a Murine Model. (18th March 2016) - Fell, Gillian L.; Cho, Bennet S.; Pan, Amy; Nose, Vania; Anez‐Bustillos, Lorenzo; Dao, Duy T.; Baker, Meredith A.; Nandivada, Prathima; Gura, Kathleen M.; Puder, Mark
Abstract : Background: Fat emulsions are important components of parenteral nutrition (PN). Fish oil (FO) emulsions reverse cholestasis in PN‐associated liver disease. There are 2 FO monographs. One is "FO; rich in omega‐3 fatty acids" (NFO). The other, "omega‐3 acids, " (PFO), is enriched in omega‐3 fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The purpose of this study is to compare the effects of 20% NFO and PFO emulsions produced in the laboratory in a murine model. Methods: Emulsions were compounded containing different oils: soybean oil (SO), NFO, and two PFOs differing in percentage of fatty acids as triglycerides (PFO66 and PFO90). Chow‐fed mice received saline, one of the above emulsions, or a commercial FO (OM) intravenously (2.4 g/kg/day) for 19 days. On day 19, animals were euthanized. Livers, spleens, and lungs were procured for histologic analysis. Results: OM, SO, NFO, and PFO90 were well‐tolerated clinically. PFO66 resulted in tachypnea and lethargy for 1 minute following injections. At euthanasia, PFO66 and PFO90 groups had organomegaly. Histologically, these groups had splenic and hepatic fat‐laden macrophages, and lungs had scattered fat deposits. Other groups had normal organs. Conclusions: PFO emulsions present an attractive possibility for improving inflammation in PN‐dependent patients by concentrating anti‐inflammatory EPA and DHA. However, 20% PFO emulsions were poorly tolerated and precipitated adverse end organ sequelae, suggesting that they may not be safe. Development of novel manufacturing methods may achieve safe 20% PFO parenteral emulsions, but by established formulation methods, these emulsions were clinically suboptimal despite meeting pharmacopeial standards.